Quality‐by‐control of intensified continuous filtration‐drying of active pharmaceutical ingredients. Issue 2 (31st October 2022) - Destro, Francesco; Barolo, Massimiliano; Nagy, Zoltan K.
Abstract: Continuous manufacturing and closed‐loop quality control are emerging technologies that are pivotal for next‐generation pharmaceutical modernization. We develop a process control framework for a continuous carousel for integrated filtration‐drying of crystallization slurries. The proposed control system includes model‐based monitoring and control routines, such as state estimation and real‐time optimization, implemented in a hierarchical, three‐layer quality‐by‐control (QbC) framework. We implement the control system in ContCarSim, a publicly available carousel simulator. We benchmark the proposed control system against simpler methods, comprising a reduced subset of the elements of the overall control system, and against open‐loop operation (the current standard in pharmaceutical manufacturing). The proposed control system demonstrates superior performance in terms of higher consistency in product quality and increased productivity, proving the benefits of closed‐loop control and of model‐based techniques in pharmaceutical manufacturing. This study represents a step forward toward end‐to‐end continuous pharmaceutical processing, and in the evolution of quality‐by‐design toward quality‐by‐control.